Analyzing Key Barriers to the Success of the Merdeka Belajar Campus Merdeka Program - Iskandar, Iskandar; Yasin, Moh Fatah; Suhaida, Dada; Yuniendel, Ratna Kasni; Rustam, Rustam; Marlianto, Ferry (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study is grounded in the premise that the full implementation of the Merdeka Belajar Kampus Merdeka (MBKM) strategy has been hindered by challenges related to insufficient human resources and inadequate infrastructure. The research aims to identify the key factors influencing the successful implementation of the MBKM program, with a focus on State Universities in West Borneo. Employing a qualitative research approach, the study gathers data primarily through in-depth interviews. The findings reveal several critical determinants affecting the program's success. These include the commitment and strategic vision of university leadership, the establishment of a dedicated unit to oversee program implementation, strong partner support and engagement, a positive attitude within the academic community towards the MBKM initiative, active and effective participation of program supervisors, proactive and innovative student involvement, contributions from academic staff in administrative roles, the availability of standardized operating procedures, and alignment between curriculum planning and program objectives.